2011
DOI: 10.1007/s00198-011-1677-z
|View full text |Cite
|
Sign up to set email alerts
|

Non-elite gymnastics participation is associated with greater bone strength, muscle size, and function in pre- and early pubertal girls

Abstract: Non-elite gymnastics participation was associated with musculoskeletal benefits in upper limb bone geometry, strength and muscle function. Differences between the two gymnastic groups emerged for arm lean mass and muscle CSA, but not for bone strength.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 37 publications
2
20
0
Order By: Relevance
“…Physical activity represents an extrinsic factor that impacts both mineral accretion and BMAT, exerting permissive capacity of the growing skeleton to achieve its full genetic potential [24]. In accordance with the consistent reports of the beneficial effects of physical activity on bone deposition in children [2530], we hypothesized that in this moderate-intensity weight-bearing physical activity intervention during a critical period of growth and development would result in augmentation of material properties of bone in terms of mineral deposition and femoral marrow cavity volume. There were no significant differences in baseline sample characteristics (Table 1).…”
Section: Resultssupporting
confidence: 52%
“…Physical activity represents an extrinsic factor that impacts both mineral accretion and BMAT, exerting permissive capacity of the growing skeleton to achieve its full genetic potential [24]. In accordance with the consistent reports of the beneficial effects of physical activity on bone deposition in children [2530], we hypothesized that in this moderate-intensity weight-bearing physical activity intervention during a critical period of growth and development would result in augmentation of material properties of bone in terms of mineral deposition and femoral marrow cavity volume. There were no significant differences in baseline sample characteristics (Table 1).…”
Section: Resultssupporting
confidence: 52%
“…All studies (except one) that demonstrated a bone strength advantage for sport groups, reported positive adaptations in both bone mass and structure. Generally, bone strength was conferred to athletes based on a larger bone area (6% to 80%; total, cortical, and medullary) or significantly larger cortices (eg, up to 26% greater cortical thickness at 38% tibia).…”
Section: Resultsmentioning
confidence: 99%
“…RCTs tended to focus on prepubertal ( n = 7) or mixed prepubertal and peripubertal groups ( n = 5); only two studies included both prepubertal and postpubertal participants . Recreational PA and organized sports studies more often assessed bone outcomes in prepubertal ( n = 2) or mixed prepubertal and peripubertal groups ( n = 8) . Fewer were conducted in postmenarcheal ( n = 4) or with mixed (prepubertal, peripubertal, and postpubertal) groups ( n = 7) .…”
Section: Resultsmentioning
confidence: 99%
“…Following findings from animals, most human skeletal exercise studies have focused on resistance training and high impact exercises (eg, jumping). Further support for these regimens comes from cross-sectional studies of athletes who regularly engage in these activities and that report almost universally that exercise-trained individuals have greater bone health than their sedentary peers (8,15,37,45). Comparisons among athletes who consistently participate in loading versus nonloading recreational activities and sports lend additional support to the potential causal role of exercise in optimizing skeletal health (8,24,28).…”
Section: Exercise In Enhancing Skeletal Gains In Children and Adolescmentioning
confidence: 99%